2004
DOI: 10.1002/ajmg.a.30028
|View full text |Cite
|
Sign up to set email alerts
|

Malignant degeneration of presacral teratoma in the Currarino anomaly

Abstract: The autosomal dominant Currarino anomaly (CA) comprises a presacral mass, partial sacral agenesis, and anorectal defects. Chronic constipation in childhood related to anorectal defects is the most common presenting symptom and hemisacrum the most frequent malformation. The presacral mass may be an anterior meningomyelocele, teratoma, hamartoma, dermoid cyst, neuroenteric cyst, or a combination of these. Sepsis and meningitis are frequent serious problems related to the anterior meningomyelocele, whilst maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 29 publications
1
40
0
6
Order By: Relevance
“…Interestingly, HLXB9 gene mutations are associated with a high rate of solid presacral tumor development such as benign teratoma (23/26 mutated patients compared to 12/24 for nonmutation carriers). Malignancy in CS has been reported in the literature for four children and for four adults [Ashcraft and Holder, 1974;Yates et al, 1983;Norum et al, 1991;O'Riordain et al, 1991;Tander et al, 1999;Martucciello et al, 2004;Urioste et al, 2004;Sen et al, 2008]. It may be consistent with recent studies detecting high levels of HLXB9 mRNA in hindgut, breast, and neuroendocrine tumor cells, suggesting a putative role of HB9 protein in particular types of tumor development [Neufing et al, 2003;Hollington et al, 2004].…”
Section: Genotype^phenotype Correlationsupporting
confidence: 72%
See 3 more Smart Citations
“…Interestingly, HLXB9 gene mutations are associated with a high rate of solid presacral tumor development such as benign teratoma (23/26 mutated patients compared to 12/24 for nonmutation carriers). Malignancy in CS has been reported in the literature for four children and for four adults [Ashcraft and Holder, 1974;Yates et al, 1983;Norum et al, 1991;O'Riordain et al, 1991;Tander et al, 1999;Martucciello et al, 2004;Urioste et al, 2004;Sen et al, 2008]. It may be consistent with recent studies detecting high levels of HLXB9 mRNA in hindgut, breast, and neuroendocrine tumor cells, suggesting a putative role of HB9 protein in particular types of tumor development [Neufing et al, 2003;Hollington et al, 2004].…”
Section: Genotype^phenotype Correlationsupporting
confidence: 72%
“…Recently, Urioste et al [2004] suggested it could be higher. This notion must be considered in genetic counseling, treatment options and follow-up of patients with CS.…”
Section: Clinical and Diagnostic Relevancementioning
confidence: 99%
See 2 more Smart Citations
“…With backing in the literature, we now recommend that asymptomatic mutation carriers should be examined with MRI (3,14,25,34), and that presacral tumours (except for small meningoceles) should be removed (3,25,34). Figure 3b and Tom Monclair (born 1942) MD PhD and specialist in paediatric and general surgery.…”
Section: Geneticsmentioning
confidence: 99%